Fragment-based design, synthesis and biological evaluation of theophylline derivatives as ATAD2 inhibitors in BT-549 cells - Dahong Yao; Jieshu You; Xuetao Yang; Jin Zhang; Xiaojun Yao (Taylor & Francis Group, 2023)
ATPase family AAA domain-containing protein 2 (ATAD2) has been emerging as a hot anti-cancer drugable target due to its oncogenic epigenetic modification closely associated with cancer cells proliferation, apoptosis, migration and drug resistance. In this study, we design a series of theophylline derivatives as novel ATAD2 inhibitors through fragment-based screening and scaffold growth strategy. A novel potent ATAD2 inhibitor (compound 19f) is discovered with an IC50 value of 0.27 μM against ATAD2, which adopts a combination of classic and atypical binding mode. Additionally, compound 19f could impede ATAD2 activity and c-Myc activation, induced significant apoptosis, and illustrated an anti-migration effect in BT-549 cells. Collectively, these results provide new enlightenment for the development of novel potent ATAD2 inhibitors for triple-negative breast cancer (TNBC) treatment.